2019
DOI: 10.2147/rmhp.s181174
|View full text |Cite
|
Sign up to set email alerts
|

<p>Equity of health workforce distribution in Thailand: an implication of concentration index</p>

Abstract: BackgroundGeographical maldistribution has been a critical concern of health workforce planning in Thailand for years. This study aimed to assess the equity of health workforce distribution in public hospitals affiliated to the Office of Permanent Secretary (OPS) of the Ministry of Public Health (MOPH) through the application of “concentration index” (CI).MethodsA cross sectional quantitative design was employed. The dataset comprised 1) health workforce data from the OPS, MOPH in 2016, 2) regional and provinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 31 publications
5
33
0
1
Order By: Relevance
“…The comparison between the two groups was based on the medium Mann–Whitney U rank sum test, and the comparison between multiple groups was based on the Kruskal–Wallis H rank sum test. For evaluating the distribution and equity of residents’ prevalence of diseases in the two weeks prior to the survey, prevalence of chronic diseases, medical treatment rate in the two weeks prior to the survey, and annual hospitalisation rate in the last year for different income groups, the concentration curve and concentration index (CI) were used for demonstration and calculation [ 39 ]. The value of CI was determined as (−1, 1).…”
Section: Methodsmentioning
confidence: 99%
“…The comparison between the two groups was based on the medium Mann–Whitney U rank sum test, and the comparison between multiple groups was based on the Kruskal–Wallis H rank sum test. For evaluating the distribution and equity of residents’ prevalence of diseases in the two weeks prior to the survey, prevalence of chronic diseases, medical treatment rate in the two weeks prior to the survey, and annual hospitalisation rate in the last year for different income groups, the concentration curve and concentration index (CI) were used for demonstration and calculation [ 39 ]. The value of CI was determined as (−1, 1).…”
Section: Methodsmentioning
confidence: 99%
“…For example, we found that U5MR of 15 deaths/1000 births across Brazil is associated with an approximate workforce level of 5 paediatric surgeons, 200 surgeons, 100 anaesthesiologists or 700 nurses/100 000 children. Geospatial analyses has help guide health workforce expansion in Thailand,24 as well as in some countries in sub-Saharan Africa 25. However, we caution that the workforce associations in Brazil may not be applicable to other countries.…”
Section: Discussionmentioning
confidence: 96%
“…Because the number of ambulatory visits and the number of physicians in secondary/tertiary hospitals in each province is approximately twice as those in community hospitals, we distributed questionnaires to physicians from community hospitals and secondary/tertiary hospitals with a ratio of 2:1 corresponding to the number of ambulatory visits and the number of physicians in each hospital level. 7,8 To identify patients' barriers to HCC surveillance, patients were divided into 2 groups, optimal and suboptimal surveillance groups. Optimal patients were de ned as having surveillance during the past two years that followed the guidelines, while suboptimal patients had not received surveillance that met the guidelines.…”
Section: Discussionmentioning
confidence: 99%